ANALISIS YURIDIS PENGESAHAN PERNIKAHAN TIDAK TERCATAT BAGI PASANGAN SUAMI-ISTRI YANG TELAH MENINGGAL DUNIA - Yusuf, Muhammad Zidan; Budi Wibowo, Muhammad Kurniawan; Pradana, Aditya Fajri Kurnia (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2024)
The purpose of this study is to show how the judge's consideration in the Religious Court Decision No. 145/Pdt.G/2023/PA.Ska which legalised an unregistered marriage between a deceased husband and wife. The type of research used is qualitative using normative juridical methodology. The research findings show that evidence supporting the existence of a valid religious marriage that has not been officially recorded in the civil registry becomes the basis for legalising the marriage after the death of both spouses. This option provides legal certainty to heirs and protects their freedoms with regard to conjugal status and inheritance. It also reflects the court's rigorous efforts to ensure equality and consistency with relevant legal standards.